2000
DOI: 10.1046/j.1525-1314.2000.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Pan‐African Wadi Haimur metamorphic sole, Eastern Desert, Egypt

Abstract: By comparison with the general features of metamorphic soles (e.g. vertical and lateral extension, metamorphic grade and diagnostic mineral parageneses, deformation and dominant rock types), it is inferred that the amphibolites, metagabbros and hornblendites of the Wadi Um Ghalaga–Wadi Haimur area in the southern part of the Eastern Desert of Egypt represent the metamorphic sole of the Wadi Haimur ophiolite belt. The overlying ultramafic rocks represent overthrusted mantle peridotite. Mineral compositions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Three main factors could serve to exclude the possibility that the Sambagawa metamorphism is responsible for the isochron age: 1) each sample retains the protogranular texture, 2) the major and trace element abundances plot on single lines with MgO abundance (Fig. 3), and 3) several reports show that clinopyroxene sometimes holds older isotopic information than garnet (Mørk and Mearns, 1986;El-Naby et al, 2000). The SmNd system in this study is strongly dependant on the modal abundance of clinopyroxene.…”
Section: The Meaning Of the Sm-nd Whole-rock Isochron Age And Origin mentioning
confidence: 82%
See 1 more Smart Citation
“…Three main factors could serve to exclude the possibility that the Sambagawa metamorphism is responsible for the isochron age: 1) each sample retains the protogranular texture, 2) the major and trace element abundances plot on single lines with MgO abundance (Fig. 3), and 3) several reports show that clinopyroxene sometimes holds older isotopic information than garnet (Mørk and Mearns, 1986;El-Naby et al, 2000). The SmNd system in this study is strongly dependant on the modal abundance of clinopyroxene.…”
Section: The Meaning Of the Sm-nd Whole-rock Isochron Age And Origin mentioning
confidence: 82%
“…The closure temperature of the Sm-Nd system in garnet is 700-750°C (Möller et al, 2002). Mørk and Mearns (1986) and El-Naby et al (2000) reported that clinopyroxene sometimes retains older isotopic information than does garnet. The closure temperature of clinopyroxene would be comparable to or higher than that of garnet.…”
Section: The Meaning Of the Sm-nd Whole-rock Isochron Age And Origin mentioning
confidence: 99%
“…Frisch and Al Shanti, 1977;Vail, 1985;Krö ner et al, 1988;Stern, 1994;Abdel Rahman, 1995;Abd El-Naby et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It is dominated by volcano-sedimentary rocks, dismembered ophiolites, and syn-and post-tectonic granitoids as shown in Fig. 1 (Stern, 1994;Abdelsalam and Stern, 1996;El-Nisr, 1997;Abd El-Naby et al, 2000;El-Kazzaz and Taylor, 2001;Ramadan et al, 2001;Abdelsalam et al, 2003). It is comprised of a 30 km wide zone of highly deformed ophiolitic assemblages, shelf metasediments, arc volcanics and volcaniclastics, and granitoids (Abdelsalam et al, 2003).…”
Section: The Allaqi-heiani Suture and The Geology Of The Study Areamentioning
confidence: 98%